Directive Speech Acts of Teacher and Students in Online Teaching Learning Interactions at SMP Ignatius Global School Palembang - Ayu Meidini; Didi Suhendi; Izzah Izzah (Journal of Social, Humanity, and Education, 2023)
Purpose: This research aimed to discuss the form and function of the directive speech acts of teacher and students in online teaching and learning interactions at SMP Ignatius Global School (IGS) Palembang. Methodology: The method used was descriptive qualitative, and the data source contained directive speech acts of teacher and students in online teaching at SMP IGS. Results: Based on the results, there were forms and functions of teacher and students’ directive speech acts. Furthermore, transactions were found in the discourse of classroom interactions. The forms of teacher directive speech acts in online teaching and learning interactions were requertives, questions, requirements, prohibitives, permissive, and advisories. Meanwhile, the forms of students’ directive speech acts are requertives, questions, and advisories. Limitations: This research is limited to discussing only the directive speech acts of teacher and students in teaching and learning interactions. Contribution: This research can contribute to the interaction of students and teacher regarding the directive speech acts in online teaching and learning interactions.